Cloning of porcine platelet glycoprotein Iba and comparison with the human homolog - Shi, M.; Qiao, J.; Shen, Y.; Lu, Y.; Chen, Younan; Cheng, J. (2012)
Glycoprotein Ib-IX-V (GPIb-IX-V) is a platelet adhesion receptor complex that initiates platelet aggregation. Glycoprotein Iba (GPIba) is the central component of the GPIb-IX-V complex, anchoring the complex to the cytoskeleton and harboring the binding site for von Willebrand factor (vWF). Previous studies suggest that the coagulation function in pigs differs from that in humans, especially with respect to the interaction between vWF and platelets. However, we have little knowledge about the function of porcine platelets, which is important with regard to studies of cardiovascular disease, clotting, and surgery that use pigs as animal models. To extend this information, we cloned and analyzed the porcine GPIba sequence. Porcine GPIba contains 1891 nucleotides and includes an open reading frame that encodes 627 amino acids. The nucleotide sequence showed 67% identity with human GPIba, whereas the deduced amino acid sequences were 59% identical. The vWF binding domain shares the highest identity among different species, whereas the PEST domain shows variations. Evaluation of platelet function by using ristocetin-induced platelet aggregation revealed remarkably lower levels of aggregation in porcine than human platelets. According to the sequence analysis and platelet aggregation tests, we propose that the function of GPIba, especially regarding the ristocetin-vWF-GPIba interaction, differs between pigs and humans. This characterization of porcine GPIba will enhance our knowledge of the porcine coagulation system. Copyright 2012 by the American Association for Laboratory Animal Science.